The Influence of Socio-Cultural Capital on Efforts to Prevent and Address Violence Against Women: Case Study of Women Victims of Violence in Bandung Regency - Sari, Hanifah Kartika; Pawitan, Gandhi (GoAcademica Research & Publishing, 2024)
Violence against women is a complex social issue with diverse causes. Economic, social, and cultural factors contribute to the occurrence of such violence. Analyzing social and cultural capital is a way to understand the root causes of violence against women. This research aims to analyze the influence of social and cultural capital on efforts to prevent and address violence against women in Bandung Regency. The method used is descriptive qualitative. The research findings indicate that the social capital influencing efforts to prevent and handle violence comes from the social networks of women victims of violence, including family, religious groups, and the Bale Istri community. However, cultural capital has a low influence on efforts to prevent and handle violence against women. The cultural capital of women victims of violence is still influenced by patriarchal culture, which forms embodied cultural capital based on long-internalized patriarchal norms and values. The internalized practice of patriarchal culture can be altered through gender and violence socialization by Bale Istri, enabling women to develop new embodied cultural capital that supports the prevention and handling of violence against women. Cultural change is an ongoing process that requires a long time; a combination of strong social capital and efforts towards cultural change can overcome various barriers in preventing and addressing violence against women (KtP).